Reformasi Konstitusi Dalam Transisi Menuju Demokrasi - Lay, Cornelis; Savirani, Amalinda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2000)
Constitutional reform is one of the most important ways undertaken by some transitional regime to establish a democratic government. This kind of reform has many models. In Spain i t is called reforma pactada-ruptura pactada involving